Dampak strategi pengendalian bencana abrasi di pantai Kabupaten Maros Provinsi Sulawesi Selatan - Nasiah Badwi; Ichsan Invanni Baharuddin; Ibrahim Abbas (Seminar Nasional LP2M UNM, 2019)
The end of end of this disaster become a popular issue abrasion due to impact on regional development. Research objectives, namely: 1) know the attitude of the Government and the community in disaster control abrasion. 2) know the attitude of the society towards a model of disaster control abrasion socialized, 3) Determine a strategy for controlling disaster of abrasion on the coast of Maros. The location of the research is on the coast of Celebes Maros. Maros there are 4 Subdistrict on the beach. Of the four sub socialisation model disaster control abrasion. Socializing is done directly to the public, and the samples are purposive each subdistrict. This is done because there is a problem between the communities by government regulations related to the prohibition of cutting down mangrove tampa earlier socialization. The results showed that: 1) the attitude of the Government quite well against natural disasters because the Agency has made disaster relief areas, and also has made rules of disaster mitigation, especially each disaster. The weakness of the Government's attitude is socializing less directly, only done representation of local authorities. But the attitude of the society towards the disaster still low abrasion, due to expansion of land farmed by converting mangrove forests. 2) attitudes towards disaster mitigation are socialized is high enough because of all the willing to carry out if there is a government program. 3) disaster control strategies i.e. abrasion with community empowerment with the extension and training to enhance the knowledge of the importance of disaster mitigation, the Government and society in cooperation.